Comparison between Collagenase Injection and Partial Fasciectomy in the Treatment of Dupuytren’s Contracture - Tay, T.K.W.; Tien, H.; Lim, E.Y.L. (World Scientific Publishing, 2015)
BACKGROUND: A comparative study between two treatment methods (collagenase injection and open partial fasciectomy) for Dupuytren's contracture. This study will determine differences in clinical outcome, complication rate and patient satisfaction.